Heavy ion induced hard errors in memory devices with sub-micron feature sizes - Koga, R.; Crain, S.; Crawford, K.; Yu, P. (2001 6th European Conference on Radiation and Its Effects on Components and Systems, 2001)
High density memory devices are sensitive to heavy ions resulting in hard errors (stuck bits). Even though their sensitivities vary, these devices with sub-micron feature sizes are not strongly affected by ion induced hard errors without any accumulation of total dose. However, their sensitivity to stuck bits appears to rise as the total dose increases to a certain level.